Analysis Ratio Profitability On the Financial Performance of PT Indofood Sukses Makmur Tbk Period 2019-2023 - M Fadlan Irfan Damanik; Azwan Bastian; Aji Haviz; Dwi Saraswati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In research this, ratio profitability compared to with performance finances of PT Indofood Sukses Makmur Tbk during period 2019–2023. Total ratio profitability used​ including Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Gross Profit Margin (GPM). The results of the study show that performance finance company has changed for five years Lastly, with ROA value remains below​ standard. This result show that improvement management assets and equity required For support growth greater profitability​ consistent in the future.